Transmigrasi Lokal di Lampung: Varian Kebijakan Perpindahan Penduduk di Indonesia - Budianto, Aan; Mustofa, Muhamad Bisri; Hasanah, Uswatun (Al-Isnad: Journal of Islamic Civilization History and Humanities, 2021)
This study aims to explore the background of the implementation of local transmigration policies in Lampung. Lampung area that has been since the colonial era has become a destination for population displacement called colonization, continues to experience an increase in the number of residents until the beginning of the independence period. The existence of a self-initiated transmigration policy caused Lampung to experience a surge in the population. The result of the analysis of this study is that the impact of population transfer to Lampung until the 1950s is getting out of control. Seen from the increasing number of forests cut down by the migrants. Another problem arises with the gathering of the community from Java. Many areas in Lampung later like to become a Colony of Java, such as Gading Rejo, Pringsewu, Kalirejo and Metro. On the other hand, the northern part of Lampung is not touched once. The unrest of the natives ulun Lampung was also contained in the customary congress in Palembang who wanted to organize Lampung with a local migration program. Starting from the 1970s, Lampung Tranmigrasi began to display results in the 1990s where the northern Lampung region began to show development. In central and southern Lampung which was dominated by agriculture, in northern Lampung began to grow community plantations. Besides, other businesses such as trade and transportation were more stretched in Lampung in the 1990s.